The Saudi National Mental Health Survey: Methodological and logistical challenges from the pilot study. Issue 3 (12th May 2017) - Shahab, Mona; Al‐Tuwaijri, Feda; Bilal, Lisa; Hyder, Sanaa; Al‐Habeeb, Abdulhameed Abdullah; Al‐Subaie, Abdullah; Mneimneh, Zeina; Pennell, Beth‐Ellen; Sampson, Nancy; Kessler, Ronald C.; Altwaijri, Yasmin
Abstract: Several challenges exist in carrying out nation‐wide epidemiological surveys in the Kingdom of Saudi Arabia (KSA) due to the unique characteristics of its population. The objectives of this report are to review these challenges and the lessons learnt about best practices in meeting these challenges from the extensive piloting of the Saudi National Mental Health Survey (SNMHS), which is being carried out as part of the World Mental Health (WMH) Survey Initiative. We focus on challenges involving sample design, instrumentation, and data collection procedures. The SNMHS will ultimately provide crucial data for health policy‐makers and mental health specialists in KSA.